LPM-N: a lumped parameter model for nitrogen leaching in agricultural lands - El-Kadi, A.I; Ling, G (Ground water, 1999)
This paper documents a lumped parameter model for the assessment of nitrogen leaching under agricultural lands. The model considers nitrogen transformation processes, climate data, and multiple irrigation and fertilizer applications. The model is efficient due to its analytical nature and the limited data requirements. The documentation introduces a PC-Windows interface module that simplifies the preparation of input data and the presentation of results. It also presents an example application of the model that compares simulated to measured nitrate values. The model is suitable for managing fertilizer applications, and for estimating leachate concentrations reaching ground water aquifers.